The influence of the Quality of Work Life, Organizational Culture, and Job Demand on Employees Engagement at PT Nusatovel Semarang Head Office - Reza - Bharata; Kurniani - Kurniani; Budi - Prasetya (Politeknik Negeri Semarang, 2021)
The study aimed to know the influence of quality of work life on employees engagement of PT Nusatovel Semarang, the influence of organizational culture on employees engagement of PT Nusatovel Semarang, the influence of job demand on employees engagement of PT Nusatovel Semarang, and the influence of quality of work life, organizational culture, and job demand on employees engagement of PT Nusatovel Semarang. The methods that used for data collection in this study were interview and questionnaires. The scale questionnaires were a agree disagree scale with 10 point scale. The sample that used in this study were 47 employees of head office of PT Nusatovel Semarang that choosen using convenience sampling technique. Used multiple linier regression technique for analyzing the data. It indicated that quality of work life had a positive and significant effect on employees engagement. Organizational culture had a positive and significant effect on employees engagement. Job demand had a possitive and not significant effect on employees engagement. Quality of work life, organizational culture, and job demands have 47.5% contribution to employees engagement. That means every 47.5% of employee engagement was explained by quality of work life, organizational culture, and job demands, while 52.5% was explained by other factors which were not observed in this study.